ТРАНСФОРМАЦІЯ СУЧАСНОЇ ВІЙНИ: ЯК ІНФОРМАЦІЙНІ ТЕХНОЛОГІЇ ЗМІНЮЮТЬ МОДЕЛІ ПУБЛІЧНОГО УПРАВЛІННЯ - Юрій ГАВРИЛЕЧКО (Herald of Khmelnytskyi National University. Economic sciences, 2026)
The article investigates the qualitative transformation of modern warfare: from classical armed confrontation to a paradigm in which information-computational systems based on artificial intelligence (AI) become the principal actors on the battlefield, while the human progressively shifts to the role of overseer. Modern war is increasingly a managerial and technological task requiring high-level cooperation between government, education, business and the military – a thesis confirmed by the empirical evidence of the Russo-Ukrainian conflict. Three stages of the evolution of armed conflict are substantiated and four defining features of the third epoch are identified: cognitive advantage through mass data processing and AI-mediated compression of the OODA (Observe–Orient–Decide–Act) decision cycle; the emergence of autonomous weapons systems (AWS) as a qualitatively new class of actors; state data centres as primary strategic strike targets; and the structural asymmetry of ethical constraints between democracies and authoritarian regimes in the development of military AI. Drawing on the experience of the Russo-Ukrainian war, the article demonstrates that the theatre of military operations has already become a laboratory of the new paradigm, confirmed by the growing share of AI-enabled FPV drones with autonomous targeting elements and the strategic role of AI integration in operational processes. The implications for public administration are analysed: the need for institutional adaptation, the formation of a state information security system, normative-legal regulation of civil servants’ use of AI, and the training of qualified AI operators for the Ministry of Defence and the civil service. Conditions for preserving meaningful human oversight of AWS as a key safeguard of legal and moral accountability are identified and policy recommendations formulated.